Dorset kulturen. Den Dansk-amerikanske ekspedition til Arktisk Canada 1954 - Meldgård, Jørgen (Kuml, 1955)
The Dorset Culture - The Danish-American Expedition to Arctic Canada 1954 In the summer of 1954, in the period from 19th May to 21st September, a series of archeological investigations was made in the central area of Arctic Canada, resulting in a noteworthy extension of our knowledge of the palæo-eskimo cultures, and in particular of the Dorset Culture. Reconnaissance and excavations were concentrated in the area af Igloolik, 69°-70°N, 80⁰-82⁰ W. The expedition was sent out by the Danish National Museum and the Pennsylvania University Museum, and was in addition sponsored by the Arctic Institute of North America. The Pennsylvania University Museum was represented by Richard Emerick, and the Danish National Museum by the present author. But the day before we started from Churchill on Hudson Bay, the "gate to the Arctic", a third member joined the expedition, Father Gui Mary-Rousseliere, a catholic missionary and, with his experience and deep interest in eskimology, an extremely welcome addition to the expedition. The main object of the expedition was to identify settlements of the Dorset Culture. In the course of the last 30 years a very large quantity of material from this culture has reached Canadian museums, while a not inconsiderable collection from North Baffin Land has come to the Danish National Museum. It was first identified and named by the Canadian anthropologist, D. Jenness, in 1925, on the basis of certain artifacts dug up by Eskimos near Cape Dorset in. Baffinland, and it was soon recognised in the literature as a culture form differing from, and less developed than, the Thule Culture. The absolute temporal relationship between the two cultures remained, however, archeologically unproven despite a number of investigations, as no definitely stratified site had been found. But the patina of the objects found and the presence of certain so-called "uncontaminated" finds with no admixture of "Thule artefacts" suggested a somewhat higher antiquity for the Dorset Culture. Its general impression was of great age, and it was soon given a place by archeologists in the sequence of development as a palæo-eskimo culture which could be compared, following upon the later large-scale excavations in Alaska, with i. a. the lpiutak Culture. The best impression of the Dorset Culture was to be gained in Greenland, where Erik Holtved excavated a considerable material in the Thule district, while Eigil Knuth identified Dorset artefacts on the beach terraces of Pearyland and NE Greenland in association with a particular form of tent ring - the first trace of the dwelling type of the culture. Finally a large series of uncontaminated Dorset settlements was found in Disko Bay in West Greenland, in the course of the Danish National Museum’s expedition in 1953. One of these in particular, Sermermiut at Jakobshavns Isfjord, gave important results, the long-awaited stratigraphy. Under a yardthick midden containing deposits of the Thule Culture lay a peat level of natural origin and without man-made remains; and under this lay the small flint implements of the Dorset Culture. But this same settlement site gave an additional bonus of great importance. Still deeper in the deposits, on the original beach level, and covered by a second sterile peat layer formed before the Dorset settlement, a third and older culture level was found. This too contained stone artefacts but of completely different forms, which had their closest parallels as far away as in Alaska. It was the artefact complex of the Sarqaq Culture, which had been identified the year before and separated out from the Dorset Culture on the basis of a find at the settlement of Sarqaq at the northern part of Disko Bay. In the course of reconnaissance in 1953 there was in addition discovered a large number of settlements from this culture, presumably that of the first inhabitants of West Greenland. As late as 1954, however (the above mentioned finds in Disko Bay being unpublished), the American archeologist, Henry B. Collins wrote: "We actually know little more about this remarkable old Eskimo culture (: Dorset Culture) than we did when Jenness first described it." The Igloolik region was chosen for the 1954 investigation for two reasons. A considerable number of Dorset artefacts from the Eskimos’ "treasure-hunting" had come into the hands of the National Museum of Canada through the medium of the missionaries there; and a very interesting find on the island of Abverdjar near Igloolik had been excavated in 1939 by the English archeologist G. W. Rowley. The second reason was that we knew that this deeply eroded limestone country showed a well developed system of raised beaches. For practical reasons Eskimos pitch their tent camps - and normally also build their houses - as near to the beach as possible. Around Igloolik the settlement sites of the Thule Culture lie now on raised beaches at levels from 3-4 metres to about 8 metres above present sea level, and in our search for the Dorset Culture we therefore started by surveying the area along the 8 metre contour. The most significant discovery of the summer was made south of Igloolik on the actual northeast corner of the American continent, near the present summer hunting station of Alarnerk. 208 rectangular depressions spread over an area of 3 sq. kms. signalised the presence of the same number of Dorset houses spread over raised terraces from 8 to 22 metres above sea-level. This number of house ruins makes Alarnerk the largest prehistoric settlement known in Arctic Canada or Greenland. I have chosen to divide Alarnerk into 5 zones, each representing a culture period, as the material collected, and therefore also the Dorset Culture itself, shows an even development from its commencement on the 22 metre terrace down to its last traces at a height of 8 metres. It is possible to characterize each of these 5 periods statistically and typologically. They are here called Periods I-V. Alarnerk revealed for the first time the house forms of the Dorset Culture, but in addition it also gave us an idea of the graves of the culture. Three different types were identified, but here the height above sea-level, or in other words their situation within the zones described, give no clue to their relative chronology. Eskimo graves merely lie somewhere "behind the settlement". And unfortunately these graves had been almost all disturbed subsequently, apparently being reused as meat depots. Only a few skeletal remains were found, though sufficient to give some idea of the physical type; this interesting question must wait, however, until the physical anthropologists have studied the material. The massive stone cists of the Thule Culture, erected on the ground surface, are certainly the prototype for one of the Dorset grave types, a short rectangular chamber with a stone floor. Less developed, and doubtless somewhat older, is a simple rounded pit dug in the ground and edged with a few stones. In these graves were found burial furnishings, artefacts of various types, apparently thrown in in no sort of order. But as in the case of the third grave form, where a gravel mound was heaped up over the inhumation, and where more care was shown in the placing of the grave furnishings, these artefacts in the graves differed from those found in the house ruins. They were often objects with particularly fine decoration, but unusable, broken or unfinished objects of a symbolic nature. At the end of July the ice broke up off Alarnerk and made it possible to sail over Foxe Basin towards Baffin Land. The expedition had brought up from the south by sledge an old whaleboat, an open boat-type of Scottish origin, such as was used from the whalers in Hudson Bay about the turn of the century, a type of boat in which the lines of the Viking ships are still to be traced. The boat was subsequently fitted with mast and sail, and received the name "Tikilik", the name known to every Eskimo in the Igloolik area for the big man with the unpronounceable name, T h e r k e I Mathiassen, who visited their country 32 years ago. The reconnaissance to the high mountainous Baffin Land confirmed the results from the flat limestone plateau around Alarnerk. Settlements of the Dorset Culture were found at a considerable number of locations, and here, where abundant stone and boulders were available as building material, the house ruins were in a better state of preservation. The combined results give the following picture of the Dorset house: its rectangular shape persists from the earliest to the latest period, its size being normally 5 by 4 metres, though a number of very large "communal houses" are found from quite early in the sequence, Period III, houses which measure up to 14 by 7 meters. Small open hearths are found on the floors, and benches along the walls. No entrance passage can be traced, but the actual interior of the house is dug out to a depth of up to a half metre below ground level. Not before the stage at which the houses of the Thule Culture appear, in Period V, are there any radical changes in the construction of the houses. From these immigrant whale-hunters they learnt in particular the dodge of the underground entrance passage, the cold trap; but in addition the houses were built narrower and with small side rooms for the hearth and for provisions, and the practice of constructing the raised benches along the end walls was adopted. The Thule people probably reached Greenland in the 12th century, which is thereby included in the neo-eskimo culture area. This event perhaps also marks the final close of the Dorset Culture, even though the possibility cannot be excluded that small groups may have continued to exist in the Dorset tradition in certain marginal areas, such as, for example, East Green land, where there are at least traces of a considerable Dorset influence late in the Thule Culture. The beginning of the culture is difficult to date. For one thing, it is at the moment not easy to state at which point it is correct to talk of a Dorset Culture, a question which depends on the definition of the culture. But if Alarnerk Period I be taken, as here, as representing its earliest phase, then the question as to the absolute age can be answered when the samples of organic materials brought back are dated in the C-14 laboratory. For the present it is possible to calculate on the basis of the rise in land levels that Period I probably developed at least 2000 years ago. This earliest form of the Dorset Culture, as we found it in Alarnerk Period I, was a surprise in itself. For on the basis of the material hitherto known two features, the so-called guide forms, had been emphasised, the presence of which should immediately identify the culture: the characteristic small harpoon heads with a rectangular shaft socket, and the flint industry with a number of typical forms. But instead of these there lay, in the houses and the middens, some hitherto unknown forms, large harpoon and lance heads with open or partly closed shaft sockets, and blades of slate dominating the flint artefacts. It is, however, clear enough that these remains represent the Dorset Culture, as on the following terraces at a lower level the objects discovered show an unbroken development, through which, for example, flint gradually supersedes slate and the typical artefact forms emerge. The development, in other words, goes in the direction of the material which up to now has reached the museums. The settlement with "typical" Dorset material was found 14-11½ metres above sea-level, forming Period IV. Here we meet a type of culture in which the inhabitants have completely adapted themselves to the hunting of sea-mammals, specialising particularly in the taking of walrus. In the final Dorset period (V) various circumstances appear to indicate a change towards a colder climate, which was probably one of the contributing causes of the collapse of the culture. Among these may be mentioned the fact that houses now begin to be built with a cold-trap and that lamps are made bigger. These are features which are more than merely chance borrowings from among the new fashions which at this period appear with the Thule Culture. Mention should be made of still another remarkable facet of the Dorset Culture, its art. As early as Alarnerk Periods I and II a definite feeling for form can be seen - the beautifully fashioned hunting implements catch the eye at once. But none of them is ornamented and not a single specimen of sculpture is found. A few specimens marking a commencement of plastic art appear for the first time in Period III. For this reason the wealth of sculpture in the following period comes as a particular surprise, forming a fully developed naturalistic art which chooses its motifs from the animal world. The sculptors have mastered the art of, with a sure hand, delineating exactly the essential characteristics of each species, from the fat little ptarmigan to the broad-snouted whale. These small sculptures are quickly produced, with no time lost on inessential detail. But this simplification results in precisely the best of primitive art - like that of the palæolithic in the Old World. The sculpture of the Dorset artists is more stylised when it reproduces the important beasts of the chase. Here magic appears to play a role; the objects have a function. Walrus, seal and polar bear take on more rigid and conventional forms, and are decorated, with a Christmas-tree design to represent the skeleton. Often only a portion of the beast is cut out, of the walrus, for example, only the snout with the mighty tusks. The probable connection of these reproductions with a form of hunting magic is supported by the discovery in graves of pairs of halved walrus tusks together with the bones of the upper jaw. The Dorset artists were not able to reproduce the human figure with the same degree of vigour, or rather, the human figure did not, on the whole, interest them, a not uncommon phenomenon in hunting societies. But here again the Dorset people literally reveal their unusual features. With an obvious joy in creation, which can only have originated in an artistic soul with more than its share of humour, portions of reindeer antler are covered with faces and portions of faces. They are deeply carved portraits, grimacing masks, covering the whole surface. And no two of them are alike. They tell us, in effect, a deal more about the bearers of the Dorset Culture than any number of skulls would do. The art of the Dorset Culture shows one particular feature which is one of the surprisingly few cultural elements which can be directly parallelled in the corresponding palæo-eskimo cultures further west in Alaska. This is the skeleton-motif on the animal figures already described. This motif is found, inter alia, in the lpiutak Culture in the same form. But it is not therefore necessary to postulate any direct connection. As has been stated, artistic expression is moreover a relatively late phenomenon in the Dorset Culture. The roots of the culture must be sought for on a basis of the earliest known material, that of Period I. And here we unfortunately remain at the moment with only a few rather uncertain indications to go on. The forms of the stone artefacts appear to point partly towards the south, to certain prehistoric lndian cultures, and partly back to the even older Sarqaq Culture of the Arctic, which, ’as stated above, can be shown in West Greenland to be older than the phase of the Dorset Culture found there. It is therefore of great significance that in 1954 we could also find traces of a very closely related form of the Sarqaq Culture in the lgloolik area. On terraces even higher than the 22 metre level of the earliest Dorset Culture lay artefacts and remains of settlements of the Sarqaq Culture. The earliest have now risen 54 metres and the latest some 36 metres above sea-level. The material from these sites is not abundant, but it is still sufficient to show a connection on the one hand with the finds from Greenland and the even earlier ones from Alaska, and on the other hand with the earliest of the objects from the Dorset Culture. With the Sarqaq Culture, with its inland orientation, we have a widespread cultural type with its roots in the Late Palæolithic cultures of the Old World, and which can very well be the basic level from which the palæo-eskimo cultures have developed, each adapting to suit its environment and its ecological possibilities, and each bearing traces of the more southerly cultures with which it came into contact. The Dorset Culture developed in Arctic Canada, and there is no reason to search for parallels and origins in Alaska, as was formerly a natural consequence of the relatively late type of objects which comprised the material found. Our knowledge of the Dorset Culture was unexpectedly extended in still another important direction, and that without even removing a spadeful of earth. This was through the legends of the lgloolik Eskimos. Eskimo legends telling of events and origins in the past are largely of so fantastic and supernatural a character that they can only be recorded because they illustrate excellently the Eskimo’s view of himself in relation to his world and to the rest of humanity - and at the same time because they are good stories. But among the legends of the lgloolik Eskimos there is a group which has a historical core: the tales of the Tunit people. We know this group of stories from throughout the eastern Eskimo region including Greenland, and the Tunits, originally interpreted as lndians, are now considered to have been the people of the Thule Culture. But the lgloolik Eskimos could add a number of additional illuminating stories and descriptions to the existing stock of legends, and it became obvious to us that the Tunit had nothing to do with the Thule Culture - they were the Dorset people! The Eskimos denied, first and foremost, that the Tunit had lived in the large houses of stone and whalebone which belong to the Thule Culture; it was their own forefathers who had lived in these. We were told consistently that the dwellings of the Tunit were oblong or square in plan; and that the wife sat by an open hearth within the doorway and prepared the food, and that they lay on a bench which was so short that they had to rest their legs vertically up the wall(!). Various sites could still be pointed out, where the Tunit had left remains of their buildings, and where one could see stone swarf from the manufacture of their weapons. They were good reindeer hunters, and could bring down the beasts on foot, armed only with a spear. But during the winter they caught seals at the breathing holes in the ice. And, as nowadays, the time of waiting could be long, and therefore to keep warm the hunter brought with him a little round stone lamp, which he set up before him on a little elevation. By leaning forward he could let his inner fur fall over the lamp, thereby forming a sort of little tent in which the temperature soon rose and warmed his body. Moreover the Tunit had often scars of burning on his stomach and breast, for, in his eagerness to harpoon the seal when it eventually appeared, it happened not infrequently that the hunter knocked over the lamp! Another important beast of the chase was the walrus, and here the legendary strength of the Tunit was a great help, not least in transporting the booty home to the village; for they had no dogs, but only a short sledge which they pulled themselves. These and other illuminating details agree exactly with the results of the archeological investigations. And in addition the stories give a much more vivid picture of the Dorset people than we could have obtained from the archeological sources alone. Jørgen Meldgård